2006
DOI: 10.1007/s00299-005-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of a PAL gene from Astragalus membranaceus var. Mongholicus and its crucial role in flux into flavonoid biosynthesis

Abstract: An important traditional Chinese medicine herb, Astragalus membranaceus var. Mongholicus, whose dried root is known as Radix astragali ("Huangqi" in Chinese), has high flavonoid content as an essential active constituent. Phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) catalyzes the first and also a rate-limiting step in phenylpropanoid pathway, which supplies precursors for a variety of secondary metabolites including flavonoids. A PAL gene, designated AmPAL1 (GenBank accession no. AY986506), was isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…The concentration of each compound was as follows: 0.602 mg/ml (1), 0.604 mg/ml (2), 0.600 mg/ml (3), 0.306 mg/ml (4), 1.086 mg/ml (5), 0.580 mg/ml (6), 0.206 mg/ml (7) and 0.202 mg/ml (8). The stock solution was further diluted with methanol to make serial concentrations for the calibration curves.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of each compound was as follows: 0.602 mg/ml (1), 0.604 mg/ml (2), 0.600 mg/ml (3), 0.306 mg/ml (4), 1.086 mg/ml (5), 0.580 mg/ml (6), 0.206 mg/ml (7) and 0.202 mg/ml (8). The stock solution was further diluted with methanol to make serial concentrations for the calibration curves.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with the increased level of PAL activity and with the accumulation of phenolic compounds measured in our experiments. Other studies showed that UV-absorbing compounds, mainly flavonoid and sinapate esters, other metabolites of the phenylpropanoid pathway, markedly accumulated upon UV-B irradiation, which is a consequence of an increase in transcription of PAL and other genes of phenylpropanoid enzymes (Shirley 1996, Liu et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…It also acts in the synthesis of main active ingredients within many plants, e.g., caffeoyl quinic acids in Coffea canephora (Mahesh et al 2006) and quercetin in Astragalus membranaceus var. mongholicus (Liu et al 2006b). Razzaque and Ellis (1977) have shown that PAL is important for rosmarinic acid biosynthesis in Coleus blumei, and Chen and Chen (2000) have suggested that this enzyme has the same role in S. miltiorrhiza.…”
Section: Introductionmentioning
confidence: 97%